Event-Triggered Strategy Design for Discrete-Time Nonlinear Quadratic Games With Disturbance Compensations: The Noncooperative Case - Yuan, Yuan; Wang, Zidong; Guo, Lei (IEEE transactions on systems, man, and cybernetics. Systems, 2018)
In this paper, the event-triggered strategy design problem is addressed for a class of discrete-time nonlinear quadratic noncooperative games subject to matched disturbances. The event-triggered scheme is proposed based on the relative error of the input signals with aim to determine whether such signals should be transmitted to the actuator or not. The disturbance-observer-based game strategy is put forward to compensate the matched disturbance and also optimize the individual cost function for each player. The main purpose of the addressed problem is to design the time-varying strategy parameters such that the upper bound of the individual cost function of each player is minimized unilaterally over a finite horizon [{0,N}] . Sufficient conditions are first established for the existence and uniqueness of the game strategies through backward Riccati-like recursions and then the desired strategy parameters are computed iteratively by utilizing the Moore-Penrose pseudo inverse. Finally, a simulation example is provided to verify the effectiveness of the proposed design method.